Optical laser microphone for human-robot interaction: speech recognition in extremely noisy service environments. (19th March 2022) - Fukumori, Takahiro; Cai, Chengkai; Zhang, Yutao; El Hafi, Lotfi; Hagiwara, Yoshinobu; Nishiura, Takanobu; Taniguchi, Tadahiro
Abstract : Domestic robots are often required to understand spoken commands in noisy environments, including service appliances' operating sounds. Most conventional domestic robots use electret condenser microphones (ECMs) to record the sound. However, the ECMs are known to be sensitive to the noise in the direction of sound arrival. The laser Doppler vibrometer (LDV), which has been widely used in the research field of measurement, has the potential to work as a new speech-input device to solve this problem. The aim of this paper is to investigate the effectiveness of using the LDV as an optical laser microphone for human-robot interaction in extremely noisy service environments. Our robot irradiates an object near a speaker with a laser and measures the vibration of the object to record the sound. We conducted three experiments to assess the performance of speech recognition using the optical laser microphone in various settings and showed stable performance in extremely noisy conditions compared with a conventional ECM. GRAPHICAL ABSTRACT: UF0001